Self Efficacy From The Quranic Perspective: The Study On Teachers Of Islamic Education At National Secondary School In Peninsular Malaysia - Noornajihan Ja‘afar; Robiatul Adawiyah Mohd @ Amat; Mahyuddin Hashim; Syed Najihuddin Syed Hassan; Nurul AsiahMuhamad; Noor Zulaili Mohd Ghazali; Widus Sempo; Nurul Wahida Fauzi (AENSI Publication, 2024)
The term of self efficacy was introduced in psychological field around 70's. However, this term is still not very prominence by most individuals, especially those who are not from psychology background. Therefore, it is very important to highlight this issue, due to its important towards the successful of oneself. Precisely, this study will explore the concept of self efficacy from the Islamic perspective. This study also was designed to examine self-efficacy (SE) teachers of Islamic Education (TIe) at national secondary schools in Peninsular Malaysia. This study used a quantitative approach and the questionnaire was the main instrument. Multi stage cluster sampling technique was used to determine the sample. The sample size involved in this research were 544 TIS representing a population of 8562 TIe national secondary school in Peninsular Malaysia. The results showed that SE of TIe were very high (min=4.32). In addition, this study has also seen to have implications for the policy and practice of teaching among TIe.